VD_FINDINFO 35/2011/DCA vom 11. März 2011 - VD Tribunal cantonal (2011)
HYPOTHÈQUE LÉGALE DES ARTISANS ET ENTREPRENEURS, PREUVE FACILITÉE | 837 al. 1 ch. 3 CC, 839 CC, 961 al. 3 CC, 101 CPC, 107 CPC, 109 al. 2 CPC, 115 CPC